Randomised controlled trials of antidepressant and anti-anxiety medications for people with autism spectrum disorder: systematic review and meta-analysis. Issue 6 (1st November 2021) - Deb, Shoumitro; Roy, Meera; Lee, Rachel; Majid, Madiha; Limbu, Bharati; Santambrogio, Jacopo; Roy, Ashok; Bertelli, Marco O.
Abstract : Background: Although widely used, the current evidence for the efficacy of antidepressant and anti-anxiety medications for people with autism spectrum disorder (ASD) is limited and conflicting. Aims: We carried out a systematic review and meta-analysis of randomised controlled trials that assessed the effectiveness of these medications in people with ASD. Method: We searched the following databases: Cochrane Library, Medline, EMBASE, CINAHL, PsycINFO, ERIC, DARE and ClinicalTrials.gov. Additionally, we hand-searched 11 relevant journals. We used the Cochrane risk-of-bias tool and Jadad score to assess the quality of each included study. We carried out a meta-analysis using a random effects model. Results: We included 15 randomised controlled trials (13 on antidepressants and two on anti-anxiety medications) for a total of 958 people with ASD. Data showed contradictory findings among the studies, with larger studies mostly showing a non-significant difference in outcomes between the treatment and the placebo groups. Meta-analysis of pooled Yale-Brown Obsessive Compulsive Scale and Clinical Global Impression Scale data from nine studies (60%) did not show any statistically significant inter-group difference on either of the outcome measures. The adverse effects reported were mild and, in most studies, their rates did not show any significant inter-group difference. Conclusions: Given the methodological flaws in the most included studies and contradictory findings, it is difficult to draw any definitive conclusion about the effectiveness of either antidepressant or anti-anxiety medications to treat either ASD core symptoms or associated behaviours. Robust, large-scale, randomised controlled trials are needed to address this issue.